Ethical trends and community care Nursing perspectives (Revista Electrónica REDINE, 2017)
Ethics has been the unquestionable basis of nursing professional practice throughout the event in any field where it is developed, incorporating systems of practices guided by knowledge, the arts and methods and the components of moral and ethical action and The human quality. The concept of community care is broad, comprehensive and little recognized and must use all the ethical and human propensities that contribute to make it a reality in the person, family and community in all dimensions. This article intends to reflect on some intrinsic tendencies in the practice of the role played in community care by community nurses and nurses. For this it is necessary to clarify the manifested and recognized definitions about community nursing, about ethical implications, community care and respect, it is imperative to develop broadly the perspective of the concept community ethical care; Using all the aspects that contribute to the care of the sick or healthy person, the family, the community group or community as it deserves, in an integral way to take into account all dimensions.
Keywords: ethical trends; nursing; care